2015
DOI: 10.1007/s11274-015-1831-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lipid accumulation and biodiesel production by oleaginous Chlorella protothecoides under a structured heterotrophic-iron (II) induction strategy

Abstract: A structured heterotrophic-iron (II) induction (HII) strategy was proposed to enhance lipid accumulation in oleaginous Chlorella protothecoides. C. protothecoides subjected to heterotrophic-iron (II) induction achieved a favorable lipid accumulation up to 62 % and a maximum lipid productivity of 820.17 mg/day, representing 2.78-fold and 3.64-fold increase respectively over heterotrophic cultivation alone. HII-induced cells produced significantly elevated levels of 16:0, 18:1(Δ9), and 18:2(Δ9,12) fatty acids (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…indicated inFig.2, the biomass productivity of T.minus increased from 240.52 to 457.01 mg L -1 d -1 at the FeC 6 H 5 O 7 ·NH 4 OH range of 0-6 mg L -1 followed by a slight that neither iron-deficiency nor iron over-supply negatively affect T.minus cell growth, which seems to be in accordance with previous study of C.protothecoides reported byLi et al (2015). According toCarmel et al(2014), deficiency of iron limits the development of plants and algae Park et al (2013).…”
supporting
confidence: 91%
“…indicated inFig.2, the biomass productivity of T.minus increased from 240.52 to 457.01 mg L -1 d -1 at the FeC 6 H 5 O 7 ·NH 4 OH range of 0-6 mg L -1 followed by a slight that neither iron-deficiency nor iron over-supply negatively affect T.minus cell growth, which seems to be in accordance with previous study of C.protothecoides reported byLi et al (2015). According toCarmel et al(2014), deficiency of iron limits the development of plants and algae Park et al (2013).…”
supporting
confidence: 91%
“…However all the reported microalgae species which could be efficiently fermented with glucose are limited to only a few unicellular microalgae species, of which Chlorella sp. are the most used (Xiong et al, 2008;Han et al, 2012;Li et al, 2015;Perez-Garcia et al, 2011). This reported T. minus is the first one of filamentous microalgae specie.…”
Section: Identification Of Heterotrophic Ability Of T Minusmentioning
confidence: 95%
“…With the prolong of the cultivation, the lipid content of biomass by autotrophy gradually increased from 25% in inoculum to about 37.9% at day 6, while the lipid content of biomass by heterotrophy decreased to 10% at day 2 and then gradually increased to only about 18.8%, much lower than that by autotrophy. Low lipid content was also observed in C. protothecoides when heterotrophic cultivation was employed (Wei et al, 2009;Li et al, 2013Li et al, , 2015. A possible reason for this phenomenon might be that the major products of biosynthesis are structural substances e.g., polysaccharides and proteins for microalgae cell construction, rather than the energy storage chemicals such as lipids in the rapid growth phase of heterotrophy with glucose.…”
Section: Identification Of Heterotrophic Ability Of T Minusmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that a high amount of lipids in microalgae biomass is essential to make biodiesel production feasible, the search for alternative techniques to increase the lipid content of microalgae is necessary. In this sense, Li et al (2015) presented a structured heterotrophic-iron (II) induction strategy for lipid accumulation in microalgae of the species Chlorella protothecoides. The authors showed that with this technique, microalgae cultured in heterotrophic medium in the presence of iron (II) were able to accumulate up to 62% of lipid on a dry basis, with a maximum productivity of 820.17 mg/ day, representing an increase of 3.21 times in the productivity, when compared with the conventional heterotrophic cultivation.…”
Section: Characterization Of Microalgae Oilmentioning
confidence: 99%